1999
DOI: 10.1088/0264-9381/16/12/308
|View full text |Cite
|
Sign up to set email alerts
|

Mass outflow rate from accretion discs around compact objects

Abstract: Abstract.We compute mass outflow rates from accretion disks around compact objects, such as neutron stars and black holes. These computations are done using combinations of exact transonic inflow and outflow solutions which may or may not form standing shock waves. Assuming that the bulk of the outflow is from the effective boundary layers of these objects, we find that the ratio of the outflow rate and inflow rate varies anywhere from a few percent to even close to a hundred percent (i.e., close to disk evacu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 39 publications
2
87
0
Order By: Relevance
“…Although continuous accreting solutions (i.e., shock-free solutions) are persistently present even for smaller energy E 1 (as expected), we do not find shocked flow solutions (or perhaps they are present but in much narrower parameter space). It can be speculated that maybe by prohibiting our jump condition in energy (energy dissipation at a shock front), we may obtain shock-driven outflows for smaller flow energy E 1 , which could be a case similar to Das & Chakrabarti (1999), where they considered little energy loss and found mass outflows in pseudo-Newtonian geometry. However, powerful outflows should carry away a significant amount of ( kinetic) energy.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Although continuous accreting solutions (i.e., shock-free solutions) are persistently present even for smaller energy E 1 (as expected), we do not find shocked flow solutions (or perhaps they are present but in much narrower parameter space). It can be speculated that maybe by prohibiting our jump condition in energy (energy dissipation at a shock front), we may obtain shock-driven outflows for smaller flow energy E 1 , which could be a case similar to Das & Chakrabarti (1999), where they considered little energy loss and found mass outflows in pseudo-Newtonian geometry. However, powerful outflows should carry away a significant amount of ( kinetic) energy.…”
Section: Discussionmentioning
confidence: 95%
“…That is, mass outflows are not suppressed by relativistic effects and energy dissipation (for a comparison with the psuedo-Newtonian case with no energy dissipation , see, e.g., Das & Chakrabarti [1999]). For a fixed angular momentum, on the other hand, a higher value of fṀ is expected from stronger shocks occurring in the inner regions, and this seems to be the case more in rotating black hole cases (see Fig.…”
Section: Dependence Of Energy and Mass Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…Chakrabarti 2,5,54 presented the first global inflow and outflow solution (GIOS) where a formalism is presented to compute the outflow rate from the inflow rate theoretically. Das and Chakrabarti 60 and Das et al 59 extended this for flows with rotation. It was found that the shock strength is intimately related to the outflow rate.…”
Section: Jets and Outflowsmentioning
confidence: 79%
“…This result may have important consequences in connection to the jet formation mechanism for Galactic relativistic sources. It has been shown that (Das 1998;Das & Chakrabarti 1999) the hot and dense postshock region of a BH accretion disk may generate accretion-powered Galactic and extragalactic outflows and that the baryonic load of such outflows increases with the increment of the postshock flow temperature and density. From Figure 2, we conclude that there must be some relationship between the normalized QPO frequencies and the amount of the baryonic content of outflows from Galactic microquasars; the details of such an investigation are reported elsewhere (Das, Rao, & Vadawale 2003).…”
Section: Governing Equations Solution Procedure and Resultsmentioning
confidence: 99%